Boundaries of Professionalization at Work: An Ethnography-inspired Study of Care Workers' Dilemmas at the Margin - Maya Christiane Flensborg Jensen (Copenhagen Business School (CBS), 2017)
Within the last decade, rehabilitation has been promoted as a new professionalization opportunity within home care policy and practice in both Denmark and across Europe. Rehabilitation is said to reconfigure home care work in ways that result in improved working conditions, better quality of services, and cost savings. Rehabilitation is, however, only the most recent example of an ongoing range of new reforms and demands that have focused on professionalizing home care workers and their areas of work by imposing new professional structures, qualifications or status on the workers. And, yet, despite these ongoing processes of professionalization, home care workers, and care workers as such, continue to be socially, technically and economically marginalized at work. This paradox has increasingly encouraged in particular feminist-inspired academics (e.g., Sullivan, 2007; Cheney and Ashcraft, 2007) to question whether we have sufficiently understood the complexities and particularities of how professionalization processes are constituted and function at work. Their studies indicate that both definitions of “professionals” and the more material modes of organizing and doing “professional” work in the west tend to privilege some workers (i.e., white, white-collar, heterosexual males) and marginalize others, especially female workers who perform “dirty”, private household services for the aging or disabled, such as home care workers. Following these studies I take a critical stance against the so-called professionalization opportunities that are offered to home care workers with the introduction of rehabilitation in home care organizations. I ask what happens to the home care workers' area of work and their risk of being socially, economically and technically marginalized, when they are confronted with the new opportunities to professionalize in rehabilitative home care organizations.
hdl:10398/9560
Keywords: 650